Dispersive Alfvén Wave Control of O+ Ion Outflow and Energy Densities in the Inner Magnetosphere. Issue 15 (5th August 2019) - Hull, A. J.; Chaston, C. C.; Bonnell, J. W.; Wygant, J. R.; Kletzing, C. A.; Reeves, G. D.; Gerrard, A.
Abstract: The relationship between dispersive Alfvén waves (DAWs), magnetospheric activity, and O + ion outflow/energy density is examined using measurements from the Van Allen Probes. We show that correlated DAW activity and O + outflow/energization is a characteristic feature of the inner magnetosphere during active conditions and during storms persists for several hours over large L‐shell and azimuthal ranges of the plasma sheet. Though enhanced during substorm and storm active periods, these correlated features are most intense during geomagnetic storms. Comparisons show a linear relationship between DAW electric (and magnetic) field energy density and outflowing O + energy. Statistical measurements from a large number of storms also reveal a linear relationship between DAW energy density and gross enhancements in energetic O + energy densities. These observations support the notion that DAWs play an important role in the energization of O + ions into and within the inner magnetosphere. Plain Language Summary: Geomagnetic storms are major disturbances in the Earth's magnetosphere, during which the particle content and pressure in the magnetosphere increase considerably. Much of the pressure increase is due to singly charged oxygen ions that come from the ionosphere. How this happens is not clear. Analyzing satellite observations, we found evidence suggesting that a particular type of low‐frequency electromagnetic wave called a dispersive Alfvén wave may be playing a key role. These waves are found to be more prevalent and intense in the magnetosphere during storms. Oxygen ion energies are shown to increase with increasing intensities of these waves. The oxygen ion contribution to pressure also increases in association with intensified wave activity. These observations support the notion that the waves energize and heat oxygen ions into and within the magnetosphere over extended periods of time, which leads to significant magnetospheric pressure increases. Key Points: Dispersive Alfven wave energy density is enhanced during substorms and geomagnetic storms Oxygen ion outflow energy and energy density are correlated with dispersive Alfven wave energy density Observations support modeling that dispersive Alfven waves enhance oxygen ion energy density in the inner magnetosphere